Parameter fisiologi kambing kacang (Capra aegagrus hircus) di Desa Nunkurus Kecamatan Kupang Timur Kabupaten Kupang - Yoseph AD Hereng; Yulfia N Selan; Filphin Adolfin Amalo (Jurnal Veteriner Nusantara, 2019)
Goat are herbivoreus ruminant animals that commonly farm in Indonesia. Goats have advantages like quick to breed and can adapt in different environments. Goats played importantely in social and culture in Nunkurus Kupang district, goat can have an important role in the field of animal husbandry in the region. The purpose of this study was to determine the physiology parameter of goat in Nunkurus. The measured parameter are body temperature, respiration and pulse. This research uses as much as 36 kacang goats. Sample are grouped into 3 groups based on age. Child group with age 2 to 8 months, young 8 to 12 months and adult >12 months. In each group consist of 6 males and 6 females. The data about fisiology value taken in morning and afternoon in one week for each aged group. The results showed that average of kacang goat body temperature in Nunkurus at the morning is 38,8 ± 0,09°C to 39,7 ± 0,05°C and at the afternoon is 38,9 ± 0,2°C to 40,1 ± 0,1°C. The respiration average at the morning is 14,28 ± 1,1 to 19,42 ± 1,1 times/minute and at the afternoon is 16,85 ± 0,48 to 21,14 ± 0,78 times/minute. The pulse at the morning is 74 ± 1,39 to 99 ± 0,9 times/minute and at the afternoon is 76 ± 1,13 to 102 ± 0,75 times/minute. It is concluded that the value of fisiology parameter in Nunkurus Village is in the same range with the other area in Indonesia.